Children Can Learn New Facts Equally Well From Interactive Media Versus Face to Face Instruction - Kwok, Kristine; Ghrear, Siba; Li, Vivian; Haddock, Taeh; Coleman, Patrick; Birch, Susan A. J. (Frontiers in Psychology, 2016)
Today’s children have more opportunities than ever before to learn from interactive technology, yet experimental research assessing the efficacy of children’s learning from interactive media in comparison to traditional learning approaches is still quite scarce. Moreover, little work has examined the efficacy of using touch-screen devices for research purposes. The current study compared children’s rate of learning factual information about animals during a face-to-face instruction from an adult female researcher versus an analogous instruction from an interactive device. Eighty-six children ages 4 through 8 years (64% male) completed the learning task in either the Face-to-Face condition (n = 43) or the Interactive Media condition (n = 43). In the Learning Phase of the experiment, which was presented as a game, children were taught novel facts about animals without being told that their memory of the facts would be tested. The facts were taught to the children either by an adult female researcher (Face-to-Face condition) or from a pre-recorded female voice represented by a cartoon Llama (Interactive Media condition). In the Testing Phase of the experiment that immediately followed, children’s memory for the taught facts was tested using a 4-option forced-choice paradigm. Children’s rate of learning was significantly above chance in both conditions and a comparison of the rates of learning across the two conditions revealed no significant differences. Learning significantly improved from age 4 to age 8, however, even the preschool-aged children performed significantly above chance, and their performance did not differ between conditions. These results suggest that, interactive media can be equally as effective as one-on-one instruction, at least under certain conditions. Moreover, these results offer support for the validity of using interactive technology to collect data for research purposes. We discuss the implications of these results for children’s learning from interactive media, parental attitudes about interactive technology, and research methods.